Training Addiction Professionals in Empirically Supported Treatments: Perspectives from the Treatment Community. Issue 1 (January 2014) - Hartzler, Bryan; Rabun, Carl
Background: Large-scale dissemination efforts seek to expand opportunities for the addiction treatment community to receive training in empirically supported treatments (ESTs). Prospective consumers of such training are valuable sources of input about content of interest, preferences for how training events are structured, and obstacles that deter receipt of training. Methods: In this mixed-method study, data were collected in 64 semistructured individual interviews with personnel during site visits to 16 community opioid treatment programs (OTPs). At each OTP, interviews were completed with the executive director, a clinical supervisor, and 2 direct-service clinicians. Topical interests were analyzed qualitatively in a cultural domain analysis. Likert ratings of training event preferences were analyzed via generalized linear mixed models (GLMMs), and unstructured interviewee comments were analyzed via narrative analysis. Obstacles to training receipt were analyzed qualitatively with both content coding and narrative analysis. Results: Based on topics of reported interest, cultural domain analysis suggests as ESTs of note: Multidimensional Family Therapy, Motivational Enhancement Therapy, Relapse Prevention Therapy, "Seeking Safety, " and broad addiction-focused pharmacotherapy. Regarding training event preferences, GLMMs and narrative analysis revealed clear preferences for time-distributed trainings and use of participatory activities (e.g., trainer demonstrations, role plays, small group exercises). Content coding identified cost as the primary obstacle to receipt of EST trainings, followed by lack of time, logistical challenges, and disinterest, and narrative analysis elaborated on contextual issues underlying these obstacles. Conclusions: As primary consumers of EST technologies, the treatment community has valuable input to offer. Dissemination efforts may be enhanced by greater consideration of their preferences for training content and event structure, as well as practical obstacles that challenge their receipt of training.